Review of Islamic Law Regarding Waqf Land Taken Back by Heirs (Case Study in Teladan Baru Village, Rundeng Subdistrict, Subulussalam City): Tinjauan Hukum Islam Mengenai Tanah Wakaf Yang Diambil Kembali Oleh Ahli Waris (Studi Kasus Di Desa Teladan Baru Kecamatan Rundeng Kota Subulussalam) - Abdullah, Arifin; Lispaini, Lispaini (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2023)
This research is motivated by the problem of Waqf Land which has been built by the Religious Affairs Office in Teladan Baru Village, Rundeng District, Subulussalam City, which one of its heirs wants to take back, due to personal interests. So researchers are interested in researching, how are people's perceptions of waqf land in Teladan Baru Village, Rundeng District, Subulussalam City and what are the provisions of Islamic Law regarding Waqf Land Reclaimed by Heirs in Teladan Baru Village, Rundeng District, Subulussalam City. The research method used in the preparation of this thesis is field research and interviews. The results in this study are the public's perception of the land donated by Pak Udin, so the community does not agree if the heirs take back the waqf land because the waqf land is still being used properly and properly, so there is no strong reason for the heirs take the waqf land again. However, the scholars of the Imam school of thought differ in terms of understanding the waqf itself, Imam Abu Hanifah is of the opinion that the assets that have been donated remain the property of the person who has made the endowment and may be withdrawn. Imam Maliki may give waqf for a certain period of time, and when the specified period passes, it is permissible for the person giving the waqf to take back the property that has been donated. Imam Syafi'i is of the opinion that the assets that have been donated are completely independent of the beneficiary who has donated them, and belong to Allah. And the Hambali school says that the waqf releases the waqf property from the ownership of the waqf property. So the Waqf Land that has been donated in Teladan Baru Village, may not be taken back by the heirs with the opinion of the previous scholars and with the reason that the heirs are not acceptable to the community and the Ministry of Religion.